Evolution of the Efficacy of the Translation Process in Translation Competence Acquisition - Hurtado Albir, Amparo (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2019)
The aim of this paper is to present PACTE’s measurement of and results for the variable “efficacy of the Translation Process” in its experiment on Translation Competence Acquisition (TCA). This is one of the variables that provide information about the acquisition of the strategic sub-competence. We define this variable as the relationship between the time taken to complete a translation task, its distribution in stages, and solution acceptability. We consider translation process efficacy to be based on an optimal relationship between solution acceptability and time, i.e. achieving maximum acceptability in minimum time. In that respect, our initial premise was that finding acceptable solutions should take less time as the TCA process advances.Our aim as regards this variable was to investigate whether, as Translation Competence is acquired, differences occur in terms of: (1) the time taken to carry out a translation task; (2) the distribution of the time spent on a translation task between stages; (3) the relationship between the time spent on a translation task and solution acceptability.